2021
DOI: 10.1186/s12905-021-01190-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling successive birth interval of women in Ethiopia: application of parametric shared frailty and accelerated failure time model

Abstract: Background Both short and long birth intervals are associated with many risk factors and about 29% of births are short birth intervals in Ethiopia. The purpose of this study is to model the birth intervals of adult women aged 15–49 years using accelerated failure time and shared frailty models in order to analyze the birth intervals of Ethiopian women. Methods The data was obtained from the 2016 Ethiopian Demographic and Health Survey (EDHS). Acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
4
4
0
Order By: Relevance
“…The region where mothers are living has also a substantial effect on recurrent birth in which the risk of recurrent birth in Afar and Oromia was lower by 34.3% and 26.4% respectively than the risk of recurrent birth of mothers in the Tigray region. These findings were supported by a study in [21] that revealed that there is a considerable birth difference across regions. A study reported in overall sub-Saharan Africa [22], Muslim mothers had a higher likelihood of recurrent birth as compared to non-Muslim mothers.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The region where mothers are living has also a substantial effect on recurrent birth in which the risk of recurrent birth in Afar and Oromia was lower by 34.3% and 26.4% respectively than the risk of recurrent birth of mothers in the Tigray region. These findings were supported by a study in [21] that revealed that there is a considerable birth difference across regions. A study reported in overall sub-Saharan Africa [22], Muslim mothers had a higher likelihood of recurrent birth as compared to non-Muslim mothers.…”
Section: Discussionsupporting
confidence: 60%
“…The estimated risk of recurrent birth of mothers from the rural area was lower than 11.5% of the estimated risk of recurrent birth of mothers from the urban area and it is supported by [23], the significant recurrent birth not only between urban and rural areas but also between zones. In contrast, a study finding in [21] reported that as compared to single mothers, the mothers whose marital status was divorced, widowed/ separated, and married had a longer birth interval, and the effect of mothers' current marital status on recurrent birth events was null.…”
Section: Discussionmentioning
confidence: 84%
“…This consistency might be because of that in this study adequate number of observations are incorporated. Like the study findings20 21 in the wealth index, contraceptive use had a significant effect on birth intervals. In this study, it was perceived that as compared with the birth intervals of mothers from a household with higher economic status, the birth intervals of mothers from a household with lower economic status had lower birth intervals.…”
Section: Discussionsupporting
confidence: 72%
“…Ultimately, formulating an effective family planning strategy requires an understanding of reproductive patterns and behaviors to ensure optimum birth spacing. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, formulating an effective family planning strategy requires an understanding of reproductive patterns and behaviors to ensure optimum birth spacing. 22 In Ethiopia, increasing the birth interval to at least 2 years reduced infant mortality by half. 23 Over the last 20 years, there has been no substantial change in the median birth interval, whereas the average birth interval has grown slightly but steadily.…”
Section: Introductionmentioning
confidence: 99%